Comparative taxonomic analysis of Pseudomonas batumici and evolutionally related species - Klochko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
Results of 16S rRNA gene sequences analysis have been shown that strain Pseudomonas batumici UCM V-321T forms a separate branch within the genus Pseudomonas and has 98% of 16S rRNA gene sequence similarity with evolutionally most related species P. gingeri and P. baetica. The differences between the mentioned species determined by the polyphasic taxonomic analysis include the presence of some enzymes, pigments production, spectra of assimilated carbon sources, fatty acid profiles, and antagonistic activity. Synthesis of antistaphylococcal antibiotic batumin was found only in P. batumici strains and is, probably, the unique peculiarity of this species.